2022
DOI: 10.1021/jacs.2c02144
|View full text |Cite
|
Sign up to set email alerts
|

Programmed Polyene Cyclization Enabled by Chromophore Disruption

Abstract: A new polyene cyclization strategy exploiting β-ionyl derivatives was developed. Photoinduced deconjugation of the extended π-system within these chromophores unveils a contrathermodynamic polyene that engages in a Heck bicyclization to afford [4.4.1]-propellanes. This cascade improves upon the limited regioselectivity achieved using existing biomimetic tactics and tolerates both electron-rich and electron-deficient (hetero)­aryl groups. The utility of this approach was demonstrated with the diverted total syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…We presume that C2À C8 bond during the isomerization (II-A) or after the formation of Z-1 may become highly strained due to the steric interactions between the substituents X and COR, which might facilitate a further photochemical rearrangement. [22] Eventually, IIA can generate the more stable resonance structure II-B to release such strain or it can be directly formed from the intermediary Z-1 under the same reaction conditions. Thus, II-B can undergo 5-exo-trig cyclization with the distal diene unit of the triene system to form further well-stabilized diradical intermediates (III-A/III-B).…”
Section: Chemistry-a European Journalmentioning
confidence: 99%
“…We presume that C2À C8 bond during the isomerization (II-A) or after the formation of Z-1 may become highly strained due to the steric interactions between the substituents X and COR, which might facilitate a further photochemical rearrangement. [22] Eventually, IIA can generate the more stable resonance structure II-B to release such strain or it can be directly formed from the intermediary Z-1 under the same reaction conditions. Thus, II-B can undergo 5-exo-trig cyclization with the distal diene unit of the triene system to form further well-stabilized diradical intermediates (III-A/III-B).…”
Section: Chemistry-a European Journalmentioning
confidence: 99%
“…In this regard, it is worthwhile to mention efficient racemic polyene cyclization strategies for the total synthesis of (±)-taxodione [(±)- 1 ] independently developed by Johnson et al (in 1982) and Harring and Livingstone (in 1992) . Recently, Frederich et al (in 2022) developed a programmed polyene cyclization enabled by chromophore disruption for unified total syntheses of abietane diterpenoid, (±)-taxodione [(±)- 1 ] and icetaxane diterpenoid, (±)-salviasperanone . Further, Vanderwal et al (in 20 2 0) reported an elegant cobalt-catalyzed stereocontrolled radical bicyclization approach to oxidized abietane diterpenoids, in particular the total syntheses of (±)-plebedipene B and (+)-2-O-deacetyl plebedipene C (in 2021) .…”
Section: Introductionmentioning
confidence: 99%
“…To date, a few synthetic approaches have given access to cyclopropanes with contiguous all-carbon quaternary centers via photochemical approaches (Scheme 1C). 58 The Gevorgyan group 59 disclosed that pyridotriazole, a diazo surrogate, could be converted to the corresponding pyridine carbene under UVlight irradiation, and this compound is capable of completing the cyclopropanation reaction. However, only one highly congested cyclopropane bearing contiguous all-carbon quaternary center was afforded.…”
Section: ■ Introductionmentioning
confidence: 99%